Deciphering the Driving Mechanism and Regulatory Strategies of Antibiotic Resistance Genes Transmission in Lead-Contaminated Soil Microbial Communities by Multiple Remediation Methods - Yafei Wang; Hang Yu; Lingwei Meng; Yuhui Cao; Zhihao Dong; Yushan Huang; Yimin Zhu; Qiao Ma; Xiaonan Liu; Wei Li (Applied Sciences)
Pb-contaminated soil poses inherent risks for the spread of antibiotic resistance genes (ARGs). However, few reports have investigated the distribution of lead resistance genes (LRGs), particularly their role in ARGs dynamics during Pb-contaminated soil remediation. This study explored the mechanisms driving ARGs variation under different remediation strategies. The results indicated that an increase in the total abundance of ARGs after applying montmorillonite (Imvite), the composite remediation agents of MgO and Ca(H2PO4)2 (MgO-Ca(H2PO4)2), and the composite remediation agents of montmorillonite, MgO, and Ca(H2PO4)2 (Imvite-MgO-Ca(H2PO4)2). Bioelectrochemical systems (BES) effectively reduced ARGs abundance, and when combined with Imvite-MgO-Ca(H2PO4)2, lowered the risk of ARGs proliferation linked to antibiotic deactivation. Changes in Pb concentration and pH reshaped microbial communities, impacting both LRGs and ARGs. To reduce the risk of ARGs proliferation and transmission during, various control strategies, such as modifying Pb stress, adjusting pH, and manipulating microbial community structure, have been proposed. The study provided theoretical foundation and practical strategies for controlling ARGs dissemination during the remediation of heavy metal-contaminated soil.